To Veil or Not to Veil - Dabbous-Sensering, Dima (2006)
This article uses critical discourse analysis (CDA) in order to analyse the discussion of the Muslim dress code (commonly referred to as the hijab) on Al Jazeera’s religious talk show A-Shari’a wal Hayat. Between 1998 and 2003, several episodes dealt with the Turkish and French ban and the ‘issue’ of the headscarf, most of them hosting prominent religious scholar Youssef Qaradawi. Drawing mostly on Fairclough’s critical analytical approach to the media, I will examine, at the micro- or local level, key linguistic strategies and rhetorical arguments deployed by participants (mostly Qaradawi, and to a lesser extent, hosts and viewers) in order to justify their position concerning the nature of the Muslim dress code. This in depth textual/local analysis will be supplemented with a brief analysis at the macro- or global level, which will look at the overall structure of these episodes in order to see the extent to which dominant positions privileged by participants at the micro level are also reinforced by the superstructure of the episodes themselves. Throughout, an intertextual analysis will be used in order to study which religious discourses from the larger socio-cultural context are drawn upon in Al-Jazeera’s discussion of the hijab. The purpose of this multi-levelled analysis is to answer the following questions: Which religious discourses on the hijab are privileged by those talk shows? Are there any differences in the range of opinions covered by the various episodes dealing with the same issue? How are the various positions, when they exist, manifested at the local/global levels of analysis? Most importantly, what do these discussions on the hijab tell us about Al-Jazeera’s self-confessed editorial line (‘the opinion and the other-opinion’) concerning one of the most controversial religious topics for Muslims?